Fitoquímica de Borreria verticillata (L.) G. Mey., Borreria ocymoides (Burm. f.) DC. e Richardia brasiliensis Gomes (Rubiaceae) - Souza, Fábio Henrique Tenório de (2013)
The genera Borreria G. Mey. and Richardia L. belong to Rubiaceae family. Borreria verticillata (vassoura-de-botão) presents indole and isoquinoline alkaloids, iridoids, sesquiterpenes and steroids. It is popularly used for diabetes, bacterial infections, eczema, rheumatism, analgesic and antipyretic. Borreria ocymoides is used to treat fungal infections and eczema and due to morphological and anatomical similarity with B. verticillata is believed that might be being used with the same purposes as B. verticillata. Although there are no reports in the chemical literature, preliminary phytochemical screening revealed the presence of saponins, tannins, glycosides and anthraquinones. Richardia brasiliensis (ervanço and poaia) presents terpenoids, flavonoids and coumarins. Ethnopharmacological studies indicate emetic, antidiabetic, anthelmintic properties and for the treatment of eczema, burns, bronchitis, influenza and hemorrhoid. This work contributed to the phytochemical family Rubiaceae using B. verticillata, B. ocymoides and R. brasiliensis. For this, the plants were collected, identified and deposited in the Prof. Lauro Pires Xavier (JPB) herbarium. Dried and pulverized, the powder plant was subjected to extraction and partitioning. Then, the phase chromatography was subjected to chromatographic and spectroscopic methods for isolation and identification of substances, respectively. B. verticillata revealed the predominance of secondary metabolites belonging to the class of terpenoids (β-sitosterol, stigmasterol, betulinic acid, alcohol betulinic, oleanolic acid, ursolic acid, uvaol and 3β-hydroxyurs-11-en-28,13-β-olide) and as porphyrin derivatives (pheophytin a, pheophytin b and 151-hydroxy-(151-S)-porphyrin lactone a). B. ocymifolia showed a predominance of phenolic substances as coumarins (scopoletin, umbelliferone and cumarieletephyn), anthraquinones (2-hydroxy-3-methoxy-6-metilantracen-9,10-dione and 2-hydroxy-3-metilantracen-9,10-dione), and p-hydroxycinnamic acid and ursolic acid, showing a different chemical profile to morphologically similar Borreria. R. brasiliensis showed the presence of terpenoids: ursolic acid and uvaol.